Effects of various exercise therapies on 6-min walk distance in patients with stable chronic obstructive pulmonary disease: a systematic review and network meta-analysis - He, Haoran; Qin, Zhikai; Liu, Kuiliang; Shen, Guilan (Frontiers in Medicine, 2025)
PurposeThis study aimed to compare the effects of various exercise interventions on the 6-min walk distance (6MWD) in patients with stable chronic obstructive pulmonary disease (COPD) using network meta-analysis and to explore their optimal dosage configurations.MethodsRandomized controlled trials (RCTs) on exercise interventions for patients with COPD published before January 1, 2025, were retrieved from CNKI, PubMed, PsycINFO, Web of Science, and the Cochrane Library. A total of 55 eligible RCTs were included. A meta-analysis and network meta-analysis (using R software) evaluated the effects of water-based exercise, traditional Chinese mind-body training, and general exercise on 6MWD. For the optimal intervention method, subgroup analysis of the conventional meta-analysis and nonlinear meta-regression were used to examine the dosage-efficacy relationship.ResultsNetwork meta-analysis showed water-based exercise (WBE) most favorably improved 6MWD (SUCRA = 98.9, MD = 83.91, 95% CI: 55.98–111.83), significantly outperforming traditional Chinese mind-body training (CTMBT) and general exercise (GE). Nonlinear meta-regression linked efficacy to dosage, with optimal outcomes achieved with ≥3 sessions/week (5 sessions as ideal), ≥60 min/session (90 min as perfect), an 8-weeks duration, and a total of 270 min/week. Patients aged ≤ 61.67 years showed more pronounced improvements.ConclusionWater-based exercise was the most effective intervention for improving the 6MWD of COPD patients. Optimal results required managing frequency (≥3 times/week, ideally 5 times/week), session duration (≥60 min, ideally 90 min), 8 weeks, and a total of 270 min/week. Older patients (≤61.67 years) benefited more. This study supported individualized, evidence-based exercise rehabilitation strategies for COPD.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42025636763, identifier CRD42025636763.